2021
DOI: 10.29241/jmk.v7i2.629
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Kepatuhan Protokol Kesehatan Covid-19 Pada Pekerja Sektor Informal Di Kota Makassar (Studi Kasus di Terminal Mallengkeri)

Abstract: Facing the adaptation of new habits (IMR) towards a productive and safe society against COVID-19, the Minister of Health issued a Minister of Health Decree number HK.01.07 / MENKES / 382/2020 concerning Health Protocols. The target in this study is the availability of a Covid-19 Health Protocol Compliance Effectiveness Study for Informal sector workers at Mallengkeri Terminal. This research is a quantitative method with cross sectional design. The research was conducted at Mallengkeri Terminal. The population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(4 reference statements)
0
1
0
1
Order By: Relevance
“…There is a positive relationship between knowledge and standard precautions. The results showed that based on the results of the analysis, the relationship between knowledge and compliance in the use of PPE has a positive correlation value, so it can be said that the better the respondent's understanding of standard precautions, the more obedient the respondent will be in the use of PPE (7).…”
Section: Resultsmentioning
confidence: 97%
“…There is a positive relationship between knowledge and standard precautions. The results showed that based on the results of the analysis, the relationship between knowledge and compliance in the use of PPE has a positive correlation value, so it can be said that the better the respondent's understanding of standard precautions, the more obedient the respondent will be in the use of PPE (7).…”
Section: Resultsmentioning
confidence: 97%
“…3 Kepatuhan adalah salah satu perilaku pemeliharaan kesehatan yaitu usaha seseorang untuk memelihara kesehatan atau menjaga kesehatan agar tidak sakit dan usaha penyembuhan apabila sakit. 4 Kepatuhan adalah istilah untuk menggambarkan perilaku pasien dalam menelan obat secara benar sesuai dosis, frekuensi, dan waktunya. Pasien dilibatkan dalam mengambil keputusan untuk menelan obat atau tidak, hal ini dilakukan untuk melatih kepatuhan.…”
Section: Oajjhsunclassified
“…Virus Corona adalah satu dari banyaknya virus yang mempunyai gejala mulai dari ringan sampai berat. Setidaknya terdapat 2 jenis COVID-19 telah diketahui bisa menimbulkan gejala yang berat seperti SARS yang terjadi di China pada tahun 2002, virus ini termasuk virus yang penularannya melalui udara ketika orang yang menderita SARS ini berbicara, batuk dan bersin (Abadi et al, 2021). Dan ada juga MERS, berasal dari timur tengah dan bisa disebut sebagai sindrom pernafasan.…”
Section: Covidunclassified